Spin-engineering of magnetic sensor structures - Yeo, Michelle Min Xue (2015)
Vast resources are being devoted to the optimization of data recording and storage, this project aims to take a peak into this huge area of growth and advancement of research and is only just a fraction of the magnitude of this area of research. Spin-engineering of magnetic sensor structures is the focus of this report. The procedures that were carried out from fabrication of sample holder, deposition ,Magneto Optical Kerr Effect measurement and Current-In-Plane measurement, aided in the understanding and measurement of the magnitude of exchange bias, coercivity and also GMR ratio. It is regrettable that a GMR ratio of only 4.9% was achieved within the course of this project, and further optimization would be needed to note the achievement of a common ratio of 5 to 10 %. However, the exchange bias noted is with the common range and reported to be in the range of 200 Oe.